Low-dose of caffeine alleviates high altitude pulmonary edema via regulating mitochondrial quality control process in AT1 cells - Tian, Liuyang; Jia, Zhilong; Yan, Yan; Jia, Qian; Shi, Wenjie; Cui, Saijia; Chen, Huining; Han, Yang; Zhao, Xiaojing; He, Kunlun (Frontiers in Pharmacology, 2023)
Backgrounds: High-altitude pulmonary edema (HAPE) is a life-threatening disease without effective drugs. Caffeine is a small molecule compound with antioxidant biological activity used to treat respiratory distress syndrome. However, it is unclear whether caffeine plays a role in alleviating HAPE. Methods: We combined a series of biological experiments and label-free quantitative proteomics analysis to detect the effect of caffeine on treating HAPE and explore its mechanism in vivo and in vitro. Results: Dry and wet weight ratio and HE staining of pulmonary tissues showed that the HAPE model was constructed successfully, and caffeine relieved pulmonary edema. The proteomic results of mice lungs indicated that regulating mitochondria might be the mechanism by which caffeine reduced HAPE. We found that caffeine blocked the reduction of ATP production and oxygen consumption rate, decreased ROS accumulation, and stabilized mitochondrial membrane potential to protect AT1 cells from oxidative stress damage under hypoxia. Caffeine promoted the PINK1/parkin-dependent mitophagy and enhanced mitochondrial fission to maintain the mitochondria quality control process. Conclusions: Low-dose of caffeine alleviated HAPE by promoting PINK1/parkin-dependent mitophagy and mitochondrial fission to control the mitochondria quality. Therefore, caffeine could be a potential treatment for HAPE.